Utilization of Safety Facilities in Building Construction Sites in Federal Capital Territory Abuja and Niger State, Nigeria - Garba, Umar; Ibrahim, D.; Karem, W.B (Journal of Sustainability and Environmental Management, 2022)
The study was designed to determine the utilization of safety facilities in building construction sites in Federal Capital territory Abuja and Niger State, Nigeria. Two research questions and two null hypotheses guided the study. A descriptive survey research design was adopted for the study. The study was conducted in FCT Abuja and Niger State, Nigeria. A total of 181 respondents consisting of 20 contractors, 71 builders and 90 tradesmen with 43 items structured questionnaire were used. The internal consistency of the questionnaire was determined using Cronbach alpha method and coefficients of A ꞊ 0.889 & B ꞊ 0.727 respectively. Weighted mean and standard deviation were used to analyze the research questions while ANOVA was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed that the respondents agreed with that of the safety facilities were utilized by the construction site worker while some were not complied. This implies that, safety facilities needs to be utilized in building construction. The findings revealed that there was significant difference in the mean ratings of the responses of the three groups of respondents (20 contractors, 71 builders and 90 tradesmen) as regard the of safety facilities. Similarly, there was no significant difference in the man ratings of the respondents as regards the extents of utilizing safety facilities in building construction sites. It was therefore recommended among others that contractors, builders and tradesmen require appropriate training/induction regularly on the use of safety facilities in building construction site base on their peculiarities. There should be appropriate information concerning the use personal protective equipment (PPE) at work to prevent accident from site. Working environment should always be cleared and kept free from all objects that can cause harm or injure the workers in building construction site.